Differential Lexical and Semantic Spreading Activation in Alzheimer's Disease. (August 2013) - Foster, Paul S.; Drago, Valeria; Yung, Raegan C.; Pearson, Jaclyn; Stringer, Kristi; Giovannetti, Tania; Libon, David; Heilman, Kenneth M.
Alzheimer's disease (AD) is known to be associated with disruption in semantic networks. Previous studies examining changes in spreading activation in AD have used a lexical decision task paradigm. We have used a paradigm based on average word frequencies obtained from the words generated on the Controlled Oral Word Association Test (COWAT) and the Animal Naming (AN) test. The COWAT and AN tests were administered to a group of 25 patients with AD and 20 control participants. We predicted that the patients with AD would have higher average word frequencies on the COWAT and AN tests than the control participants. The results indicated that the AD group generated words with a higher average word frequency on the AN test but a lower average word frequency on the COWAT. The reasons for the discrepancy in average word frequencies on the AN test and COWAT are discussed.